2015
DOI: 10.7243/2059-0008-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Global metabolomic profiles reveal differences in oxidative stress and inflammation pathways in smokers and moist snuff consumers

Abstract: Background: The existing US epidemiological data show that long-term cigarette smokers are at higher risk of developing serious diseases relative to moist snuff consumers. To understand the effects of tobacco consumption, global metabolomic profiles were generated. Here, we describe metabolomic changes in oxidative stress and inflammation pathways. Methods: Matching plasma, urine, and saliva samples from chronic/long-term smokers (SMK), moist snuff consumers (MSC), and non-tobacco consumers (NTC), 40 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…In addition to the aforementioned metabolic pathway perturbations, we also observed that glutathione metabolism was significantly enriched in plasma and urine of SMK. Glutathione metabolism plays an important role in alleviating oxidative stress, 43 and this finding is consistent with our previous observation from single metabolite analyses 12 that SMK exhibited higher levels of oxidative stress. In addition, SMK exhibited elevated levels of 1,5-AG in urine, relative to MSC and NTC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to the aforementioned metabolic pathway perturbations, we also observed that glutathione metabolism was significantly enriched in plasma and urine of SMK. Glutathione metabolism plays an important role in alleviating oxidative stress, 43 and this finding is consistent with our previous observation from single metabolite analyses 12 that SMK exhibited higher levels of oxidative stress. In addition, SMK exhibited elevated levels of 1,5-AG in urine, relative to MSC and NTC.…”
Section: Discussionsupporting
confidence: 91%
“…Perturbations in caffeine metabolism, energy metabolism, and arginine metabolism distinguished the 3 different cohorts. These findings, taken together with our previous investigations, 11-13,24 provide a more comprehensive understanding of biochemical and physiological changes induced by consumption of various tobacco products.…”
Section: Introductionsupporting
confidence: 69%
“…Chronic smoking has been reported to impact functioning of multiple organs and hence, normal physiology. Numerous biochemical changes at the molecular level that could collectively drive physiological perturbations, and ultimately progression to disease states have been identified (Buro-Auriemma et al 2013, Besingi and Johansson 2014, Gao et al 2015, Prasad et al 2015, Titz et al 2015. These molecular changes encompass epigenetic, transcriptomic, proteomic and metabolomic perturbations, and map to distinct biochemical pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In efforts to identify novel candidate biomarkers of tobacco effect and gain insights into the molecular changes resulting from long-term consumption of different tobacco product categories, we utilized 'omic' technologies. Recently, we showed that global metabolomic profiles from NTC and MSC are similar, but the smokers' profiles are distinct (Prasad et al 2015). Since cigarette smoking is known to be associated with changes in DNA methylation status of select loci and globally (Shenker et al 2013, Sun et al 2013, Tsaprouni et al 2014, Teschendorff et al 2015, Gao et al 2016), here we sought to characterize global methylation changes in the buccal cells of chronic smokers and MSC.…”
Section: Introductionmentioning
confidence: 99%
“…40 Metabolic differences have been reported between smokers and snuff users but the molecular/proteomic alterations between smokers and tobacco chewers are not well elucidated. 41 A recent study employed microarray analysis to elucidate gene expression differences in peripheral blood mononuclear cells (PBMCs) obtained from smokers and moist snuff users. 42 They reported differential expression of several genes including aryl-hydrocarbon receptor repressor (AHRR), G protein-coupled receptor 15 (GPR15), leucine rich repeat neuronal 3 (LRNN3), cochlin (COCH) and serine protease 23 (PRSS23) in smokers compared to moist snuff users.…”
Section: Introductionmentioning
confidence: 99%